Plasma branched-chain amino acids and risk of radiation-induced acute skin toxicity in women with breast cancer: results from the ATHENA project - Sharma, Sukshma; Bracone, Francesca; Di Castelnuovo, Augusto; Ruggiero, Emilia; De Curtis, Amalia; Cerletti, Chiara; de Gaetano, Giovanni; Deodato, Francesco; Macchia, Gabriella; Boccardi, Mariangela; Cilla, Savino; Morganti, Alessio Giuseppe; et al. (Frontiers in Oncology, 2025)
Background/ObjectivesLittle is known regarding the influence of circulating plasma branched-chain amino acids (BCAAs) such as leucine, isoleucine, and valine on acute skin toxicity (AST) after breast cancer (BC) radiotherapy. Hence, this study examined the association between circulating plasma BCAAs and the risk of ≥ grade 2 AST post-radiotherapy among BC patients.MethodsAn observational study was conducted among 161 BC patients treated with radiotherapy within the ATHENA project in Italy. Plasma BCAAs were measured at 2-time points: at baseline (T0) and at the end of radiotherapy (T1) (after 3 or 5 weeks), and were ascertained using a validated method based on tandem mass spectrometry. AST was measured at T1 and defined according to the Radiation Therapy Oncology Group/European Organization for Research and Treatment Cancer (RTOG/EORTC) criteria. Analysis was conducted in two parts with separate study designs using multivariable-adjusted logistic regression models: 1) A cross-sectional analysis explored the association between plasma BCAAs at T1 and odds of AST post-radiotherapy; 2) A prospective analysis examined the association between plasma BCAAs at T0 and odds of AST post-radiotherapy.ResultsAST post-radiotherapy was observed in 45 (28%) patients. In the cross-sectional analysis, at T1, plasma isoleucine (1-SD increment) was associated with 43% reduced odds of ≥ grade 2 AST post-radiotherapy (OR = 0.57;95% CI 0.36 to 0.91). A similar trend was observed in the prospective analysis at T0 (OR = 0.65;95% CI 0.42 to 1.02). There was no evidence of an association between plasma leucine and valine with AST post-radiotherapy, either at T0 or T1. Plasma isoleucine was associated with lower odds of AST post-radiotherapy in BC patients.ConclusionsThe findings highlight that plasma isoleucine is associated with a low risk of ≥ grade 2 AST post-radiotherapy among BC patients. However, further studies such as isoleucine supplementation trials are needed to validate these findings.